Phosphatidylcholine composition of endotracheal tube aspirates of neonates and subsequent respiratory disease. Issue 4 (April 1992) - Ashton, M R; Postle, A D; Hall, M A; Smith, S L; Kelly, F J; Normand, I C
Abstract : The phosphatidylcholine (PC) content of the initial endotracheal tube aspirate was measured in 105 infants intubated for resuscitation or for ventilation for respiratory distress syndrome, using high performance liquid chromatography and postcolumn fluorescence derivitization with diphenyl-1, 3, 5-hexatriene. Sixty eight had measurable PC. Of the infants who developed respiratory distress syndrome, with or without subsequent chronic lung disease, neither the percentage of dipalmitoylphosphatidylcholine (DPPC) nor the ratio of DPPC to palmitoyloleoylphosphatidylcholine (POPC), showed any correlation with gestational age. However, both parameters were significantly lower overall in this group than in the group of infants who did not develop respiratory distress syndrome. Infants with a ratio of DPPC:POPC less than 3.0 developed respiratory distress syndrome irrespective of gestational age, but there was considerable overlap between groups for values greater than this. The infants with respiratory distress syndrome who went on to develop chronic lung disease had the same initial PC profile as those with respiratory distress syndrome who did not develop chronic lung disease, but differed as a group by being lighter and more premature. The development of chronic lung disease was not associated with a particular initial PC composition. Other factors related to increasing prematurity must therefore be involved in rendering infants vulnerable to developing chronic lung disease.